Calcium Signaling Dynamics in Vascular Cells and Their Dysregulation in Vascular Disease - Chang Dai; Raouf A. Khalil (Biomolecules)
Calcium (Ca2+) signaling is a fundamental regulatory mechanism controlling essential processes in the endothelium, vascular smooth muscle cells (VSMCs), and the extracellular matrix (ECM), including maintaining the endothelial barrier, modulation of vascular tone, and vascular remodeling. Cytosolic free Ca2+ concentration is tightly regulated by a balance between Ca2+ mobilization mechanisms, including Ca2+ release from the intracellular stores in the sarcoplasmic/endoplasmic reticulum and Ca2+ entry via voltage-dependent, transient-receptor potential, and store-operated Ca2+ channels, and Ca2+ elimination pathways including Ca2+ extrusion by the plasma membrane Ca2+-ATPase and Na+/Ca2+ exchanger and Ca2+ re-uptake by the sarco(endo)plasmic reticulum Ca2+-ATPase and the mitochondria. Some cell membranes/organelles are multifunctional and have both Ca2+ mobilization and Ca2+ removal pathways. Also, the individual Ca2+ handling pathways could be integrated to function in a regenerative, capacitative, cooperative, bidirectional, or reciprocal feed-forward or feed-back manner. Disruption of these pathways causes dysregulation of the Ca2+ signaling dynamics and leads to pathological cardiovascular conditions such as hypertension, coronary artery disease, atherosclerosis, and vascular calcification. In the endothelium, dysregulated Ca2+ signaling impairs nitric oxide production, reduces vasodilatory capacity, and increases vascular permeability. In VSMCs, Ca2+-dependent phosphorylation of the myosin light chain and Ca2+ sensitization by protein kinase-C (PKC) and Rho-kinase (ROCK) increase vascular tone and could lead to increased blood pressure and hypertension. Ca2+ activation of matrix metalloproteinases causes collagen/elastin imbalance and promotes vascular remodeling. Ca2+-dependent immune cell activation, leukocyte infiltration, and cholesterol accumulation by macrophages promote foam cell formation and atherosclerotic plaque progression. Chronic increases in VSMCs Ca2+ promote phenotypic switching to mesenchymal cells and osteogenic transformation and thereby accelerate vascular calcification and plaque instability. Emerging therapeutic strategies targeting these Ca2+-dependent mechanisms, including Ca2+ channel blockers and PKC and ROCK inhibitors, hold promise for restoring Ca2+ homeostasis and mitigating vascular disease progression.